Value chain analysis: an iterative and relational approach for agri-food chains. Issue 3 (9th May 2016) - Howieson, Janet; Lawley, Meredith; Hastings, Kathleen
Abstract : Purpose: Value Chain Analysis (VCA) is established as a diagnostic tool. The purpose of this study is to extend existing applications and develop an iterative and relational method. to facilitate the application of VCA to agri-food chains as a strategic process rather than a diagnostic tool. Design/methodology/approach: Using a multiple case study design, the new approach to VCA was applied to four Australian prawn fisheries. These fisheries varied in size, location, management structures and marketing arrangements and allowed the general applicability of the approach to be explored. Findings: The application of the revised VCA revealed the importance of undertaking a strategic approach, with the outcome for all fisheries being a greater understanding of their consumers and an enhanced realisation of commercial opportunities. Two fisheries completed the revised VCA, and the findings show that a relational approach is crucial in creating value. In addition, it was shown that formalised structures and the informal behaviours of the value chain members have a strong positive impact on the relationship process. Research limitations/implications: The research furthers the value chain literature and contributes an iterative approach to the application of VCA. The research also shows that obtaining improvements is not achievable for all chains, and, if the entire chain is not engaged with the process, the value of the results will be compromised. Further research is needed to confirm the validity of findings in other food industries. Originality/value: The relational approach is an original contribution to the area of VCA research and provides industry with a blueprint for creating successful value chains. Specifically, the areas of implementation and evaluation make an original contribution to the theoretical and practical knowledge of value chains.